Identification and function of long non-coding RNAs. - Young, R; Ponting, C (2013)
It is now clear that eukaryotic cells produce many thousands of non-coding RNAs. The least well-studied of these are longer than 200 nt and are known as lncRNAs (long non-coding RNAs). These loci are of particular interest as their biological relevance remains uncertain. Sequencing projects have identified thousands of these loci in a variety of species, from flies to humans. Genome-wide scans for functionality, such as evolutionary and expression analyses, suggest that many of these molecules have functional roles to play in the cell. Nevertheless, only a handful of lncRNAs have been experimentally investigated, and most of these appear to possess roles in regulating gene expression at a variety of different levels. Several lncRNAs have also been implicated in cancer. This evidence suggests that lncRNAs represent a new class of non-coding gene whose importance should become clearer upon further experimental investigation.